Inhibition of glucose-stimulated insulin release by alpha 2-adrenoceptor activation is parallelled by both a repolarization and a reduction in cytoplasmic free Ca2+ concentration. - Nilsson, T; Arkhammar, P; Rorsman, P; Berggren, P (1988)
Effects of the alpha 2-adrenergic agonist clonidine on insulin release, membrane potential, and cytoplasmic free Ca2+ concentration ([Ca2+]i) were investigated using pancreatic beta-cells isolated from obese hyperglycemic mice. Addition of 2 microM clonidine promptly inhibited glucose-stimulated insulin release, an effect accompanied by a lowering in both membrane potential and [Ca2+]i. Within minutes, the effect on Ca2+ was partly reversed, [Ca2+]i attaining a new level, although still significantly lower than in the absence of agonist. This late increase in [Ca2+]i was inhibited by 50 microM D-600, a blocker of voltage-activated Ca2+ channels. The inhibitory effects of clonidine on membrane potential, [Ca2+]i, and insulin release were abolished by 5 microM of the alpha 2-adrenergic antagonist yohimbine. Depolarization with high K+ increased [Ca2+]i also in the presence of clonidine, conditions accompanied by only a minute release of insulin. Secretion was, however, partly restored by subsequent addition of 20 mM glucose. Addition of 5 mM Ca2+ transiently reversed the effects of clonidine on both membrane potential and [Ca2+]i. Although the clonidine-induced repolarization should be enough for closing the voltage-activated Ca2+ channels with a resulting decrease in [Ca2+]i, a direct interaction of the agonist with these channels cannot be excluded. The fact that it was possible to increase [Ca2+]i with only a minor effect on insulin release suggests that the inhibitory effect of clonidine not only is due to a reduction in [Ca2+]i, but also involves interference with some more distal step in the insulin secretory machinery.